Mikrotik Hotspot Network Implementation Using Simple Queue As Bandwidth Management: Mikrotik Hotspot Network Implementation Using Simple Queue As Bandwidth Management - Mhd Billy Sandi Saragih; Indra Gunawan; Ika Okta Kirana; Sumarno Sumarno; Hendry Qurniawan (Jurnal Mantik, 2020)
Internet network is one of the most important needs in a company to access online in uploading or downloading a file. Where almost all companies already use computers and use the network as a tool to facilitate work. The problem that often occurs in the use of internet networks is that the speed is unstable, because users or users of the same network are more than one person, causing internet splits to split and not focus on one user. Mikrotik is a company that stands and makes products such as Routers, Switches, Antennas. By using a proxy router, the author found a solution to solve the problem by doing a bandweed mechanism with the aim of preventing the monopoly of bandwidth usage, so that all users or users in one network can get their bandwidth in a fair manner. Bandwidth management is a method used to meet these needs. And to do the settings, the author uses the Winbox application and also the queue function to do the implementation of the proxy router. The author uses the ip address of each computer that is connected in one network, to be used as data and then processed in the Winbox application, for bandwidth management.